Pengaruh Roe, Suku Bunga, Nilai Tukar terhadap Harga Saham Perusahaan Pertambangan yang Terdaftar di BEI - Ayu Nuryani; Furtasan Ali Yusuf; Kenedi Kenedi (Lembaga Pengembangan Kinerja Dosen, 2025)
The mining industry has become one of the hopes for the economic advancement of the nation. In the electric vehicle industry, Indonesia's metal and mineral raw material industry also contributes to the supply of raw materials for electric vehicles (EVs). This presents an attractive opportunity for investors to purchase shares in mining companies. This research aims to determine the long-term and short-term effects of Return on Equity (ROE), interest rates, and exchange rates on the stock prices of mining companies in the metal and mineral sub-industry (B146) listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2019. The study employs a quantitative method and utilizes data analysis techniques with the assistance of Eviews-12, using a sample of 49 observations. The results indicate that ROE, interest rates, and exchange rates do not have a significant impact on stock prices in the short term. However, ROE and interest rates have a negative effect on stock prices in the long term, while exchange rates have a positive effect on stock prices in the long term.